The Proceedings of the Second International Conference on Communications, Signal Processing, and Systems - Zhang, Baoju; Mu, Jiasong; Wang, Wei; Liang, Qilian; Pi, Yiming (Lecture Notes in Electrical Engineering, 2014)
The Proceedings of The Second International Conference on Communications, Signal Processing, and Systems provides the state-of-art developments of Communications, Signal Processing, and Systems. The conference covered such topics as wireless communications, networks, systems, signal processing for communications. This book is a collection of contributions coming out of The Second International Conference on Communications, Signal Processing, and Systems (CSPS) held September 2013 in Tianjin, China.